Differential immunological effects of silica nanoparticles on peripheral blood mononuclear cells of silicosis patients and controls - Ganesan, Nirosha; Ronsmans, Steven; Hoet, Peter (Frontiers in Immunology, 2022)
Silicosis is a fibrotic disease caused by the inhalation of respirable silica particles, which are typically engulfed by alveolar macrophages and subsequently induce the release of inflammatory cytokines. Various animal experimental and human studies have focused on modeling silicosis, to assess the interactions of macrophages and other cell types with silica particles. There is still, however, limited knowledge on the differential response upon silica-exposure between silicosis patients and controls. We focused on studying the responsiveness of peripheral blood mononuclear cells (PBMCs) to silica nanoparticles (SiNPs) - Ludox and NM-200 - of silicosis patients and controls. The proliferative capacity of T- CD3+ and B- CD19+ cells, were evaluated via Carboxyfluorescein succinimidyl ester (CFSE) assay. The activation status of lymphocyte subsets and response to silica were also evaluated by comparing the extent of micro-granuloma or aggregate formation with the cytokine secretion profiles between both groups of individuals. The proliferative capacity of CD19+ cells was elevated in silicotic patients as opposed to controls. Subsets of regulatory T cells (CD4+ CD25+ and CD8+ CD25+) and immunoglobulins IgM and IgG were also significantly increased in patients. The number and the size of aggregates formed were higher with SiNPs stimulation in patients compared to controls. Multivariable analysis also elucidated the role of key cytokines like interleukin-1β (IL-1β), IL-6 and interferon-gamma (IFN-γ), which were upregulated in SiNP-stimulated PBMCs of patients compared to controls. Our ex vivo model thus has potential to provide insights into the immunological effects of silica particles in lymphocytes of silicosis patients and controls.